Magnolia Parks : into the dark - Hastings, Jessa (Hastings, Jessa. Magnolia Parks universe, 2024)
"Magnolia and BJ are reeling from a devastating loss as they try to plan what's been dubbed "the wedding of the century". As family tensions mount and their respective pasts begin catching up to them, they finally have to look the truth in the eye: Can they learn to trust and be with one another again, or will they die trying?"--